Effect of the Particle Size on TDA Shear Strength Parameters in Triaxial Tests - Hany El Naggar; Khaled Zahran (Buildings, 2021)
Tire recycling and reuse in North America and worldwide have increased considerably, intending to reduce the harmful effects of scrap tires on the environment. Accordingly, the use of tire derived aggregates (TDA) as backfill material in civil engineering applications is on the rise at an unprecedented rate. However, to use TDA in the construction industry, its strength and stiffness parameters properties must be evaluated. One key factor that is known to influence the strength and stiffness of backfill material is the particle size of the used material. Hence, in this paper, a series of large-scale triaxial tests on five TDA samples with different maximum particle size, Dmax, of 19.05, 25.4, 38.1, 50.8 and 76.2 mm were conducted to investigate the effect of the particle size on the obtained results. The tests were done under consolidated drained conditions using three confining pressures of 50, 100, and 200 kPa. The results showed that the shear strength of TDA increase by increasing the maximum particle size while the cohesion did not show a specific trend. Moreover, the samples exhibited an increase in the secant elastic modulus by increasing the particle size.